IN VITRO ANTI-OXIDATIVE ACTIVITIES OF THE VARIOUS PARTS OF PARKIA BIGLOBOSA AND GC-MS ANALYSIS OF EXTRACTS WITH HIGH ACTIVITY - Ibrahim, M A; Koorbanally, N A; Islam, M S (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The anti-oxidative activities of sequentially extracted solvent fractions of different parts of P. biglobosa were evaluated in a series of in vitro assays. Our findings indicated that all extracts had electron donating and free radical scavenging activities. But the ethanol (EtOH) extracts from all the parts demonstrated more promising anti-oxidative effects in these experimental models. Apart from the aqueous extracts of the stem bark and leaves, all other extracts exhibited hydroxyl radical scavenging (HRS) activity but the ethyl acetate (EtOAc) extract of the stem bark and EtOH extracts of the root and leaves possessed more powerful HRS activity than other corresponding extracts in the parts. Further, nitric oxide (NO) inhibition activities were observed in all the extracts except the EtOAc extract of the stem bark which showed pro-oxidative activity. However, the EtOH extract of the stem bark and root as well as the EtOAc extract of the leaves displayed more potent anti-NO activity than other extracts in the parts. The GC-MS analysis of the EtOH extracts revealed that the most abundant phytochemicals are pyrogallol derivatives. Data from this study suggest that the EtOH extracts from different parts of P. biglobosa contained potent anti-oxidative agents and pyrogallol could be the main bioactive constituent.